Video research in disciplinary literacies - Ortlieb, Evan; Shanahan, Lynn E.; McVee, Mary B. (Emerald, 2015)
This edited volume provides a collection of research-based chapters that reflect the state of the art for video reflection in literacy settings. The volume foregrounds explorations of disciplinary literacies and discourses in teacher education and pre-K-12 classrooms. Authors explore literacy and use of video in relation to English Language Arts, math, science, social studies, and educational administration across a variety of contexts ranging from a preschool classroom, to a high school, to preservice and inservice teacher education and development. In their research-based studies, authors address topics of disciplinary literacy, identity, discourses or multimodality. Some chapters present research findings while others are specifically devoted to methodological concerns and addresses how researchers who wish to carry out literacy investigations using video can work through challenges in research, design, or analysis.
Keywords: Education -- General.; Education.; Visual education.; Literacy.; elektronické knihy; electronic books